Thermal Tourism, Attractiveness And Governance In A Mountain Municipality, Perspective Of Local Populations: The Case Of Hammam-Guergour In Algeria - Fertas, Lahcene; Benmahamed, Hamid; Alouat, Mohamed (Technium Social Sciences Journal, 2022)
Tourism activity plays a major role in the socio-economic development of territories, and especially more active and crucial in vulnerable regions such as mountainous areas. The purpose of this article is to participate in the development of thermal and mountain tourism in the municipality of Hammam-Guergour. It puts together the scientific literature on the topic and unveils the bond breaks of the population’s socioeconomic and political connections that obstruct the tourism image. In the multi-criteria analysis, economic indicators were not only inappropriate to the development of tourism attractiveness, but also to the living environment indicators of the population reflecting a lack of satisfaction. The participation of the population in the decision-making process remains very disadvantageous, delaying the liberation of the region. A new vision of tourism policy focusing on direct participation of local residents (participatory tourism) would stimulate tourism activities in the municipality.